Factors Associated with Uptake of Intermittent Preventive Treatment of Malaria in Pregnancy: A Cross-Sectional Study in Private Health Facilities in Tema Metropolis, Ghana - Selina Amankwah; Francis Anto (Journal of Tropical Medicine, 2019)
Introduction. Intermittent preventive treatment of malaria in pregnancy with sulfadoxine pyrimethamine (IPTp-SP) is effective in preventing the adverse consequences of malaria on birth outcomes. Methods. A cross-sectional survey was carried out among antenatal and postnatal women and midwives at private health facilities in Tema using the mixed method to investigate factors associated with uptake of IPTp-SP. Antenatal and postnatal women were consecutively enrolled and data on their sociodemographic characteristics and antenatal service utilization collected using a questionnaire and review of antenatal care (ANC) records. In-depth interviews involving attending midwives were conducted and data on ANC service delivery collected. The interviews were manually analyzed. Bivariate and multiple logistic regression analyses were done to determine factors associated with uptake of SP. Results. Of the 382 respondents, 178 (46.6%) took ≥ 3 doses of SP. Uptake was similar for those who had delivered and those yet to deliver (χ2 =2.94, p > 0.05). Ninety-seven of the 176 (55.1%) women who initiated antenatal visit during the first trimester received ≥ 3 doses of SP whilst 42.0% (76/181) of those who started during the second trimester received ≥ 3 doses (χ2 = 5.64, p = 0.02). Those who initiated ANC during the second trimester received more doses compared to those who started during the third trimester (χ2 = 4.43, p = 0.04). Respondents who attended ANC > 5 times increased their uptake by 83% compared to those who attended < 5 times (OR 0.2, 95% C.I 0.12-0.31). There was poor adherence to directly observed treatment and low knowledge of midwives on IPTp-SP protocol. Conclusion. Early initiation and regular visit to antenatal care centres promoted uptake of optimal doses of SP.